Merchandising jako nowoczesna metoda w zarządzaniu sprzedażą detaliczną - Tarczydło, Beata (Merchandising as a new method of retailing management, 2005)
The lecture presents merchandising as a new method of retailing management. The most important role of merchandising is connected with the company's effectiveness and client's satisfaction. In Poland its importance is still growing. The result of the research shows that a lot of companies do not have their regular merchandising policy. That's why the author describes definition, roots, aims and tools of the company's effective merchandising strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 369-377